The history of zhuyou healing practices: in search of data for the reconstruction of the ritual scheme - Muchowska, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
The article addresses the issue of Thunder rituals employed in Taoist zhuyou healing practices, which constituted a formal branch of Chinese medicine from the 13th to the 16th centuries. Subsequently, these rituals lost their prominence and were predominantly practiced as part of folk medicine and folk Daoism. The article serves as a contribution to the reconstruction of the schema of Thunder rituals within zhuyou practices, based on textual data from several unpublished manuscript source texts, primarily the Zhuyou ke 05953 manuscript from the National Central Library of Taiwan and the Unschuld 8070 manuscript from the Staatsbibliothek zu Berlin – Preußischer Kulturbesitz. Both manuscripts date from the 19th century, and although they contain earlier textual material, they should be interpreted primarily as evidence of ritual practices from the 18th–19th centuries. The article provides edited excerpts from these and other source texts, which contain significant cognitive data regarding the course and specifics of these rituals. These excerpts offer valuable information about certain aspects of the healing ritual practices as well as the associated beliefs. The texts also cite incantations. Notably, in these healing rituals, the Yellow Emperor assumes the role of the deity issuing decrees against disease demons. The article attempts to provide a general outline of the basic structure of zhuyou healing rituals, drawing on the textual evidence presented. These data are juxtaposed with findings from earlier studies on Thunder rituals, particularly the works of Florian Reiter and Philip Cho. The methodology of source text content analysis was employed for the purpose of this research, augmented by elements of discourse analysis, hermeneutics, and semiotics.

Artykuł poświęcony jest problematyce rytuałów Gromu stosowanych w taoistycznych praktykach leczniczych zhuyou, które od XIII do XVI w. stanowiły jeden z oficjalnych działów medycyny chińskiej. W późniejszym okresie straciły swoją rangę i uprawiane były głównie w ramach medycyny ludowej i ludowego taoizmu. Artykuł może być przyczynkiem do rekonstrukcji schematu rytuałów Gromu w praktykach zhuyou na podstawie treści zawartych w kilku niepublikowanych rękopiśmiennych tekstach źródłowych, w tym przede wszystkim w rękopisie Zhuyou ke 05953 z kolekcji Narodowej Centralnej Biblioteki Tajwanu i w rękopisie Unschuld 8070 z kolekcji Staatsbibliothek zu Berlin – Preußischer Kulturbesitz. Oba te rękopisy pochodzą z XIX w. i chociaż zawierają również wcześniejszy materiał tekstowy, to wydaje się, że powinny być interpretowane przede wszystkim jako świadectwo praktyk rytualnych XVIII–XIX w. W artykule edytowane są ustępy tych i innych tekstów źródłowych, w których zapisane zostały istotne pod względem poznawczym dane na temat przebiegu i specyfiki tych rytuałów. Cytaty te dostarczają cennych informacji na temat niektórych aspektów praktyki rytuałów leczniczych, jak również związanych z nimi wierzeń. Przytaczane są w nich również zaklęcia. Co istotne, w tych leczniczych rytuałach rolę bóstwa wydającego dekrety przeciw demonom choroby pełni Żółty Cesarz. W artykule podjęta została próba ogólnego zarysowania podstawowej struktury leczniczych rytuałów zhuyou na podstawie wskazanych świadectw tekstowych. Dane te konfrontowane są z danymi z wcześniejszych badań rytuałów Gromu, w szczególności z prac autorstwa Floriana Reitera i Philipa Cho. Do celów badawczych zastosowano metodologię analizy treści tekstów źródłowych wzbogaconą o elementy analizy dyskursu, hermeneutyki i semiotyki.
Historia praktyk leczniczych zhuyou: w poszukiwaniu danych do rekonstrukcji schematu rytuału
Keywords: zhuyou rituals; Thunder rituals; talismans (fu 符) in zhuyou practices; folk Taoism; rytuały zhuyou; rytuały Gromu; talizmany (fu 符 ) w praktykach zhuyou; ludowy taoizm